Reforming the moral subject : ethics and sexuality in Central Europe, 1890-1930 - Matysik, Tracie (Cornell University Press, 2008)
"Reforming the Moral Subject explores a movement known as "ethics reform" that flourished in Central Europe between 1890 and 1930. Tracie Matysik examines the works of German-speaking intellectuals and activists - moral philosophers, sociologists, legal theorists, pedagogy specialists, psychoanalysts, sexual liberationists, and others - who discovered in the language of ethics a means to revitalize the public sphere." "Matysik's compelling intellectual and cultural history of ethics and moral subjectivity reframes the nature of German liberalism and intellectual activism from the end of the nineteenth century until the interwar period."--Jacket